Algebra, book one, elementary course, modern edition / A. M. Welchons; W. R. Krickenberger; Helen R. Pearson - Welchons, A. M. (Massachusetts: ginn and company, 1970)
Representing, numbers and number relations, subtraction and division of real numbre, terms, like terms, evaluating an algebraic expression, chapter review and test; sentences, using more than one axiom, algebraic representation, solving problems by algebra, angles, kinds of agles complementary angles, suplemetary angles, kinds of triangles inequalities with addition and subtrabtraction axioms, chapter review and test,arithmetic test; formulas, area of a cirele, volumeof a rectangular solid, making formulas fron rules, making formulas from tables, simplifying formulaschapter review and tests, general revew, arithmetic test; positive and negative numbers, reduciong frantions lowest terms, multiplication and division of fractions, combining fractions, chapter review and tests, general review, arithmetic test; more equations and problems, compound sentences, grapha of compound sentences, algebraic representation, problems, percentage problems, chapter review and tests, general review; operations with polynimials, simplifying expressions containing parentheses, enclosing terms in parentheses, chapter review and tests, general review; equations containing parentheses, the word" sum" principle of levers, chapter review and test, geeral review cumulative test; equations containing fractions, literal equations, ration, proportions, chater review and tests, general review, cumulative test; additional work with polynomials, dividing a polynomial by a polynomal, checking division, chapter review and tests, general review, cumulative tests; graphs, graphing compound sentences, cgapterreview and tests, general review; systems of linear equations, solving problems by systems of equations, chapter review and tests, general review; special products and factoring, factoring the difference of two squares, types of factoring, complete factoring, chapter review and tests, general review, cumulative test;usng special products and factoring in silving equations, digit problems, chapter review and tests, general review;fraction, changingmixed numbers to fractions, changing fractions into mixed expressions, complex fractions, chapter review and tests, general review; fractional equations, wind and river problems, chapter review and tests, general review; powers, roots, and redicals, multiplying polynomials, rationalizing denominators, equation containing radicals, chapter review and tests, general review; quadratic equations, solving cubic equations graphically, chapter review and tests, general review; proportion ad variation, some everyday instances of variation, mucical retions, chapter review and tests, general review comulative; numerical trigonometry, the cosine of an angle, using the cosine of an angle, interpolation, general review, chapter tests, cumulative tests; review by topics statistical graphs, rounding off numbers, the ber graph, pictographs, the circle graph, line graphs.
Index, photography, graphic, practical exercise
Col. Educ
Keywords: 1. ALGEBRA 2. OPERATION FACTORING 3. NUMERICAL TRIGONOMETRIC 4. EDUCACIÓN